2022
DOI: 10.2147/vhrm.s380463
|View full text |Cite
|
Sign up to set email alerts
|

Enlargement of the Left Atrium Strongly Predicts Postoperative Mortality Following Heart Valve Surgery

Abstract: Background Enlargement of the left atrium has been thoroughly studied in many clinical situations, especially its association with mortality and morbidity. Patients and Methods The study cohort included patients with rheumatic valve pathology such as stenosis and regurgitation. All patients underwent valvular surgical procedures including mitral valve replacement (MVR), aortic valve replacement (AVR), AVR with coronary artery bypass grafting (CABG), MVR with CABG, or AV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…We have previously reported a strong association between left atrial enlargement and mortality after isolated CABG and valve surgery [ 18 , 19 ]. Our study also showed an association between left atrial enlargement and prolonged ICU stay.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported a strong association between left atrial enlargement and mortality after isolated CABG and valve surgery [ 18 , 19 ]. Our study also showed an association between left atrial enlargement and prolonged ICU stay.…”
Section: Discussionmentioning
confidence: 99%
“…Left atriomegaly often leads to left ventricular compression, resulting in significant respiratory disorders and heart failure. Significant left atrial (LA) dilation is a factor that prevents the restoration of sinus rhythm and increases the risk of thromboembolic complications [4,5,6,7].…”
Section: клінічний випадокmentioning
confidence: 99%
“…Left atriomegaly often leads to left ventricular compression, resulting in significant respiratory disorders and heart failure. Significant left atrial (LA) dilation is a factor that prevents the restoration of sinus rhythm and increases the risk of thromboembolic complications [4,5,6,7].A critically small left ventricle (LV) cavity in mitral restenosis is an additional risk factor for surgical interventions in the correction of mitral defects, since it requires adequate selection of a mechanical prosthesis if it is impossible to use a bioprosthesis due to the presence of large-sized tracks of prostheses [1]. Combination of all the К ЛІНІЧНИЙ ВИПАДОК…”
mentioning
confidence: 99%
See 1 more Smart Citation